Hypothermia treatment preserves mitochondrial integrity and viability of cardiomyocytes after ischaemic reperfusion injury. Issue 2 (February 2015) - Huang, Chien-Hua; Chiang, Chih-Yen; Pen, Ren-How; Tsai, Min-Shan; Chen, Huei-Wen; Hsu, Chiung-Yuan; Wang, Tzung-Dau; Ma, Matthew Huei-Ming; Chen, Shyr-Chyr; Chen, Wen-Jone
Abstract Background Haemorrhagic shock after traumatic injury carries a high mortality. Therapeutic hypothermia has been widely used in critical illness to improve the outcome in haemorrhagic shock by activation of cardiac pro-survival signalling pathways. However, the role played by the mitochondria in the cardioprotective effects of therapeutic hypothermia remains unclear. We investigated the effects of therapeutic hypothermia on mitochondrial function and integrity after haemorrhagic shock using an in vitro ischaemia-reperfusion model. Methods H9c2 cardiomyocytes received a simulated ischaemic reperfusion injury under normothermic (37 °C) and hypothermic (31 °C) conditions. The cardiomyocytes were treated with hypoxic condition for 18 h in serum-free, glucose-free culture medium at pH 6.9 and then shifted to re-oxygenation status for 6 h in serum-containing cell culture medium at pH 7.4. Cellular survival, mitochondrial integrity, energy metabolism and calcium homeostasis were studied. Results Hypothermia treatment lessened cell death (15.0 ± 12.7 vs. 31.9 ± 11.8%, P = 0.025) and preserved mitochondrial number (81.3 ± 17.4 vs. 45.2 ± 6.6, P = 0.03) against simulated ischaemic reperfusion injury. Hypothermia treatment ameliorated calcium overload in the intracellular (1.5 ± 0.2 vs. 9.5 ± 2.8, P < 0.001) and intra-mitochondrial (1.0 ± 0.3 vs. 1.6 ± 0.3, P = 0.014) compartments against the injury. Mitochondrial integrity was more preserved by hypothermia treatment (50.1 ± 26.6 vs. 14.8 ± 13.0%, P < 0.01) after the injury. Mitochondrial ATP concentrations were maintained with hypothermia treatment after injury (16.7 ± 9.5 vs. 6.1 ± 5.1 μM, P < 0.01). Conclusions Hypothermia treatment at 31 °C can ameliorate cardiomyocyte damage caused by simulated ischaemic reperfusion injuries. Mitochondrial calcium homeostasis, energy metabolism, and membrane integrity are preserved and play critical roles during therapeutic hypothermia treatment.